Self-reported health, persistent symptoms, and daily activities 2 years after hospitalization for COVID-19 - Alhasan, Roda; Rafsten, Lena; Larsson, Alexandra C.; Sunnerhagen, Katharina S.; Persson, Hanna C. (Frontiers in Cellular Neuroscience, 2025)
IntroductionSince the onset of the COVID-19 pandemic, 775 million cases have been reported globally. While many individuals recover fully, a significant proportion develop persistent symptoms. Numerous studies have investigated the long-term symptoms of COVID-19; however, the full extent and impact of these symptoms remain inadequately understood. The aim of this study was to investigate the prevalence of self-reported persistent symptoms, focusing on respiratory symptoms and fatigue and the impact on functional status 2 years after hospitalization for COVID-19.MethodsThis study is prospective and includes participants from a longitudinal multi-center cohort that follows patients previously hospitalized due to COVID-19 (n = 211). The current study encompasses the 2-year follow-up, using post-hospitalization questionnaire surveys. Analyzed data were collected before discharge and at the 2-year follow-up. Participants were grouped by age, sex and COVID-19 severity and group comparisons where conducted. Logistic regression analysis was used to study functional impairment.ResultsTwo years after hospital discharge due to COVID-19, 125 participants completed the 2-year follow-up. The mean age of participants was 66 years (SD 12.2), and 68% were male. The majority of participants reported present respiratory symptoms (n = 83, 69%) and fatigue (n = 98, 78%) at the 2-year follow-up. Persistent respiratory symptoms and fatigue impacted functional status substantially (p = <0.001, p = 0.028, respectively). No significant differences were observed among groups depending on age, sex, or severity of COVID-19.ConclusionFor some individuals regardless of age, sex or COVID-19 severity, respiratory symptoms and fatigue may persist for up to 2 years following COVID-19. Hence, having available support from professionals knowledgeable about COVID-19 is imperative. Further research is important to unravel the mechanisms of long-term symptoms following COVID-19 and to develop effective therapeutic and rehabilitative interventions.